EVALUATION OF THE USE OF A MANUAL TO SUPPORT A LARGE-SCALE IMPLEMENTATION OF THE "ESTRATÉGIA AMAMENTA E ALIMENTA BRASIL" - Gláubia Rocha Barbosa Relvas; Gabriela dos Santos Buccini; Sonia Isoyama Venancio (Universidade do Estado do Rio de Janeiro, 2019)
Objective: To evaluate the implementation of the Tutor Support Manual of Estratégia Amamenta e Alimenta (EAAB) - the "Manual", developed to support continuing education activities (CEA) in primary health care. Methods: Evaluative research with a quantitative and qualitative approach. The evaluated intervention consisted of the use of the Manual by the tutors of Embu das Artes-SP. The Manual proposes the development of five CEA with the health team. The data collection, before and after the intervention, comprised: 1) knowledge test for tutors and health workers; 2) questionnaire with the managers of the basic health units (UBS) on the implementation of the intervention and compliance with the EAAB certification criteria proposed by the Ministry of Health. A listening workshop was held with key informants on the use of the Manual. A quantitative analysis of the implementation indicators and a qualitative analysis of the listening workshop were used. Results: The Manual was used by eight out of 13 tutors. The median of CEA performed at the UBSs was 5 [0-5]. The mean number of correct answers of the tutors (pre 31.43 ± 5.25; post 34.86 ± 4.45; p=0.021) and workers (pre 26.09 ± 4.45; post 30.28 ± 3.55; p=0.002) in the final knowledge test was higher than in the initial test. The number of certification criteria reached by UBSs was higher in the post-intervention period (median: pre 3 [1-6]; post 5 [3-6]) and was consistent with the perception of changes by managers, as well as with the number of CEA conducted by tutors. Conclusions: The use of the Manual improved the knowledge of tutors and health workers and promoted positive changes in the work process of the teams. DOI: 10.12957/demetra.2019.43322